2012
DOI: 10.1111/j.1600-0722.2012.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel nonsense mutation in MSX1 causes tooth agenesis with cleft lip in a Chinese family

Abstract: Tooth agenesis is one of the most common developmental disorders in humans. Previous studies have attributed non-syndromic tooth agenesis to mutations in several genes, including MSX1, PAX9, EDA, and AXIN2. In this study, we investigated a Chinese family with tooth agenesis combined with cleft lip. Genomic DNA was isolated from blood samples of all available family members. Candidate genes MSX1 and PAX9 were amplified by the PCR and directly sequenced. A novel heterozygous mutation at c.C565T, exon 2 of MSX1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype. 16,38 Mutant proteins were predicted to either exhibit reduced stability or to have reduced DNA binding capacity, or to have reduced capability to interact with their cognate protein factors. As a result, the function of MSX1 as a transcriptional repressor can be greatly impaired.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype. 16,38 Mutant proteins were predicted to either exhibit reduced stability or to have reduced DNA binding capacity, or to have reduced capability to interact with their cognate protein factors. As a result, the function of MSX1 as a transcriptional repressor can be greatly impaired.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…9 Up to now, two reports propose MSX1 as a candidate gene for tooth agenesis combined with orofacial clefting. 16,41 FROM GENOTYPE TO PHENOTYPE Overview of human MSX1 mutations Since the first MSX1 variant was identified in a pedigree with tooth agenesis, 8 several additional pathogenic variants have been discovered. To analyze the MSX1 mutations, we retrieved all MSX1 variants from HGMD (Human Gene Mutation Database) Professional up to the 30th of June, 2015.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19] To date, only a few studies have addressed the genetic basis of oral cleft with or without tooth agenesis in humans. [20][21][22] Van den Boogaard et al 20 and Liang et al 21 suggested that tooth agenesis and oral cleft were associated with nonsense mutations of MSX1, such as Ser104stop in exon 1 in a Dutch family and Q189X in exon 2 in a Chinese family, respectively. However, Liang et al 21 also reported that sequence analysis of PAX9 did not reveal mutation in any of the affected individuals studied.…”
Section: Introductionmentioning
confidence: 99%